The Effect of Leadership Style on Motivation to Improve the Employee Performance - Hanifah Hanifah; Novi Indah Susanthi; Agus Setiawan (Institut Transportasi dan Logistik Trisakti, 2014)
Human resources (HR) is one of the most important factor in an organization, especially for PT. PELNI, a prominent goverment-owned marine transportation company.This study aims to determine the factors which can improve the performance of employees at PT.PELNI. Upon getting feed back from 78 employees, it is obvious that the company has apparently been successful in motivating its employees to demonstrate good performance. Success indication can be seen from the regression coefficient X2 (Work Motivation) of 0.428. While the regression coefficient X1 (Leadership Style) of 0.357. This indicates that the motivation influences employee performance greater than leadership. Accordingly, PT. Pelni can be taken as an example of a good company in motivating its employees.